Analysis of the Effect of Per capita Income, Total Consumption and Economic Growth in Regencies/Cities of Central Kalimantan Province - Rosaria Sihite (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2019)
This study aims to analyze and prove how much influence the variables of Per capita Income, Total Consumption, and Economic Growth have on people's welfare in the Regency/City of Central Borneo Province in 2015-2019. Data collection using themethod Library Research sourced from the Central Statistics Agency (BPS) of Central Borneo Province. The data in this study used secondary data. The data used is in the form of panel data, which is a combination oftime seriesdata and data cross section. The prerequisite test for data analysis used the program eviews 8.  The results of this study indicate that Per capita income has a positive and significant effect on the welfare of the people in the Regency/City of Central Borneo Province. The amount of consumption has a positive and significant impact on the welfare of the people in the Regency/City of Central Borneo Province. Economic growth has a positive and insignificant effect on the welfare of the people in the Regency/City of Central Borneo Province